Evaluation the Effect of Low Power Laser Irradiation on Healing of Induced Tendon Injuries in Rabbits - A Alkhilani, Majid; M Atta, Nabeh (The Iraqi Journal of Veterinary Medicine, 2020)
This study aimed to evaluate the efficacy of diode laser in accelerating the healing process of ‎injured tendons and to determine the best ‎irradiation doses for impulse and continuous laser ‎irradiation. The semimembranosus muscle tendon of forty mature local breed rabbits ‎‎(Oryctolagus cuniculus) of both sexes was partially injured under ‎general anesthesia. The rabbits ‎were randomized into five groups and treated on the first day postoperatively. Group C served ‎as a control and ‎received no treatment, while groups A, B, and D were subjected to diode ‎impulse laser with a power of 2×10-3 watts and a wavelength of 904 ‎nm for 15, 25, and 35 ‎min per session, respectively. Group E received continuous diode laser for 30 min per ‎session with a power of 3×10-3 watts and a wavelength of 904 ‎nm. The treated groups received irradiation for 5, 8, ‎‎15, and 21 days postoperatively. Subsequent healing processes were ‎assessed macroscopically ‎and microscopically at each time point. In treated groups versus the control group, epitenon ‎thickness increased ‎from day 5, inflammatory and fibroblast cell responses were more evident, ‎and collagen fibers were clearer and more differentiated. On day 15, when the remodeling ‎stage began, group B healed best. The impulse diode laser was found to be more effective than ‎the ‎continuous diode laser in promoting the healing of surgical defects of the tendons at varying ‎degrees. In the continuous diode laser group, ‎there was a sustained high cellular response until ‎day 21 with the appearance of unorganized and irregular collagen fibers. This study ‎‎demonstrated that diode laser can accelerate the healing process of injured tendons and that ‎impulse diode laser is more effective than ‎continuous diode laser.